Clinical profile of patients with heart failure can predict rehospitalization and quality of life. Issue 3 (March 2018) - Di Mauro, Michele; Petroni, Renata; Clemente, Daniela; Foschi, Massimiliano; Tancredi, Fabrizio; Camponetti, Virginia; Gallina, Sabina; Calafiore, Antonio M.; Penco, Maria; Romano, Silvio
Abstract : Background: The aim of this retrospective study was to identify clinical, humoral and echocardiographic variables predicting rehospitalization and poor quality of life (QOL) in patients with reduced or mid-range ejection fraction heart failure. Methods: From 2009 to 2012, 310 patients were admitted having signs and symptoms of heart failure with reduced ejection fraction. All the patients were followed by phone, calling the patients or the referring general practitioner. The Minnesota Living with Heart Failure Questionnaire (MLHFQ) was used as the instrument to evaluate QOL: MLHFQ less than 24 is a good QOL, 24–45 is moderate QOL and more than 45 is poor QOL. The primary event was poor QOL and/or rehospitalization at 4 years. Results: Seventy-nine patients died at median time of 21 months; 4-year survival was 72 ± 3%. Rehospitalization due to heart failure was recorded in 60 cases. Among 231 survivors, MLHFQ score was good in 99 (42%), moderate in 50 (21%) and poor in 88 (37%). Four-year freedom from death, poor QOL or rehospitalization was 51 ± 3%. Multivariable analysis identified the following risk factors: heart rate at discharge at least 70 bpm, ischemic heart disease, atrial fibrillation, hypercholesterolemia, chronic pulmonary disease, N-terminal pro brain natriuretic peptide at discharge, severe tricuspid regurgitation and mitral regurgitation more than moderate. Conclusion: Clinical, laboratory and echocardiographic profile is crucial to predict long-term QOL of patients admitted for heart failure.